Сложенката καλοκαγαθία во преводната книжевност на латински јазик - Kochovska-Stevovikj, Svetlana (Филозофски факултет-Скопје, 2016)
This paper investigates the Latin equivalents of the Ancient Greek compound καλοκἀγαθία in the literary translations into Latin. The translation equivalents of the noun are analysed in a corpus which consists of Latin translations of the writings: Xenophon’s Cyropaedia, Agesilaus, Constitution of the Lacedaimonians, Memorabilia and Symposium, Aristotle’s Eudemian Ethics, Nicomachean Ethics, Magna Moralia and Politics, Demosthenes’s On the Crown, Against Aristogiton and Exordia, Isocrates’ To Demonicus, Diogenes Laertius’ Lives and Opinions of Eminent Philosophers, Plutarch’s Parallel lives and Polybius’ History. Most of these translations originate from the late Middle Ages, and some of them date from the early modern period. Their authors are distinguished humanists and philologists, such as Francesco Filelfo, Basilios Bessarion, Denis Lambin, Giorgo Valla, Ambrogio Traversari, Hieronymus Wolf etc. The analysis shows various translation solutions which can be divided into four groups based on their grammatical characteristics: translation equivalents linguistically realized with one similar-meaning noun or a substantivized adjective (probitas, bonitas, virtus, honestum, integritas and elegantia); translation equivalents realized with two or more nouns or substantivized adjectives (honestas et/ ac probitas/honestas probitasque; virtus et/ac honestas; virtus et/atque probitas; bonitas ac fortitudo; aequum et bonum; pulchrum et bonum; virtus, bonitas et probitas); translations with a nominal phrase (perfecta honestas, consummata honestas, proba honestas, honesta bonitas, eximia bonitas, excellens bonitas, honesta probitas, praestans probitas, absoluta probitas, probitas morum, studium pulchri bonique, laudis et honesti studium, honesti studium, laus benignitatis and facta bona), and translations with a periphrastic expression. The choice of units points to three different interpretations of the meaning of the compound: καλοκἀγαθία is a quality with an exclusively ethical dimension (probitas, aequum et bonum, eximia bonitas, praestans probitas etc.), καλοκἀγαθία is an aesthetically-ethical ideal (studium pulchri bonique, forma et virtute praestans etc.)
Keywords: καλοκἀγαθία, translation solutions, Latin language